Two United States Olympic Committee olympism programs: Team USA Ambassador Program and Olympic Day (The Sport Journal, 2011)
The United States Olympic Committee administers a number of programs with the objective of spreading Olympism and the Olympic Ideals. Outlined below are its two most robust Olympism programs: the Team USA Ambassador Program and Olympic Day.